A Visitor of Tropical Waters: First Record of a Clymene Dolphin (Stenella clymene) Off the Patagonian Coast of Argentina, With Comments on Diet and Metazoan Parasites - Hernández-Orts, Jesús S.; Hernández-Mena, David I.; Pantoja, Camila; Kuchta, Roman; García, Néstor A.; Crespo, Enrique A.; Loizaga, Rocío (Frontiers in Marine Science, 2021)
The poorly known Clymene dolphin (Stenella clymene) is a small oceanic cetacean distributed in tropical and subtropical waters of the Atlantic Ocean. In this study, we report, for the first time, a vagrant individual of Clymene dolphin in Argentina (Rada Tilly) that represents the current southern-most record for this cetacean species. We provide a molecular identification of the dolphin, based on partial sequences of the mitochondrial cytochrome b gene, generated from DNA extracted from its metazoan parasites. Three prey species, namely Argentine hake, Patagonian squid and lobster krill were identified from hard pieces collected in the stomach. Seven metazoan parasite taxa (three in adult stage, one immature stage and three in larval stage) were identified using morphological and molecular data, i.e., the digenean Pholeter gastrophilus (new host record), the cestodes Tetrabothrius (Tetrabothrius) forsteri, Clistobothrium grimaldii¸ unidentified phyllobothriid plerocercoids, the nematodes Anisakis pegreffii (new host record), Halocercus delphini and the acanthocephalan Corynosoma australe (new host record). Our study provides the first molecular exploration of the metazoan parasite diversity in delphinids from the southwestern Atlantic, and contributes significantly to understand the poorly known parasite fauna of the Clymene dolphin.